Optical imaging of the spontaneous depolarization wave in the mouse embryo: origins and pharmacological nature. (26th March 2013) - Momose‐Sato, Yoko; Sato, Katsushige
Abstract : Spontaneous embryonic movements, called embryonic motility, are produced by correlated spontaneous activity in the cranial and spinal nerves, which is driven by brainstem and spinal networks. Using optical imaging with a voltage‐sensitive dye, we revealed previously in the chick and rat embryos that this correlated activity is a widely propagating wave of neural depolarization, which we termed the depolarization wave . One important consideration is whether a depolarization wave with similar characteristics occurs in other species, especially in different mammals. Here, we provide evidence for the existence of the depolarization wave in the mouse embryo by summarizing spatiotemporal characteristics and pharmacological natures of the widely propagating wave activity. The findings show that a synchronized wave with common characteristics is expressed in different species, suggesting its fundamental roles in neural development.